(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article presents the results of the analysis and systematization of long-term forest pathological studies (2022–2024) of pistachio stands in southern Kyrgyzstan. The influence of natural and anthropogenic factors on their sanitary condition and ecosystem stability has been identified. The necessity of comprehensive monitoring for early detection of pest outbreaks and forecasting of the phytosanitary state is substantiated. The results of the study confirm that a combination of regular monitoring, sanitary cleaning, and rational forest management ensures the stability of pistachio forests and contributes to the preservation of their ecological and resource value under the conditions of southern Kyrgyzstan.